Kjell Goldmann, Jan Hallenberg, Bengt Jacobsson, Ulrika Morth, Alexa Robertson, internationalisering, Lund: Studentlitteratur, 1999, 228 s.; Sven Bislev, En ny og større verden? Globaliseringens ansigter, København: Fremad, 1999, 127 s., kr. 198,00. - Bo Kaspersen, Lars (Politica, 2000)
-